2021
DOI: 10.3390/polym13193210
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Paclitaxel and Resveratrol Loaded Soluplus Polymeric Nanoparticles for Improved BBB Penetration for Glioma Management

Abstract: Gliomas are one of the prominent cancers of the central nervous system with limited therapeutic modalities. The present investigation evaluated the synergistic effect of paclitaxel (PAX) and resveratrol (RESV)-loaded Soluplus polymeric nanoparticles (PNPs) against glioma cell lines along with in vivo pharmacokinetics and brain distribution study. PAX-RESV-loaded PNPs were prepared by the thin film hydration technique and optimized for different dependent and independent variables by using DoE (Design-Expert) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Brain distribution and bioavailability of paclitaxel‐resveratrol PNPs compared to pure paclitaxel and resveratrol significantly boosted in mice and augmented anti‐glioma efficacy with enhanced therapeutic component solubility. In addition, this study suggested that the paclitaxel‐resveratrol PNPs cause a reduction of drug release in plasma and can reach the target site 87 . A study found that when MCF‐7 and CAL‐51 cells (human TNBC lines) were treated with TAM/RES–LbL‐LCNPs, which are nanoparticles that deliver tamoxifen and resveratrol using a layer‐by‐layer approach and liquid crystalline nanoparticle technology, it resulted in the suppression of cell growth and the induction of cell cycle arrest specifically in the G0/G1 phase.…”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 84%
See 1 more Smart Citation
“…Brain distribution and bioavailability of paclitaxel‐resveratrol PNPs compared to pure paclitaxel and resveratrol significantly boosted in mice and augmented anti‐glioma efficacy with enhanced therapeutic component solubility. In addition, this study suggested that the paclitaxel‐resveratrol PNPs cause a reduction of drug release in plasma and can reach the target site 87 . A study found that when MCF‐7 and CAL‐51 cells (human TNBC lines) were treated with TAM/RES–LbL‐LCNPs, which are nanoparticles that deliver tamoxifen and resveratrol using a layer‐by‐layer approach and liquid crystalline nanoparticle technology, it resulted in the suppression of cell growth and the induction of cell cycle arrest specifically in the G0/G1 phase.…”
Section: Advancements In Natural Substance Enhancement Through Nanote...mentioning
confidence: 84%
“…In addition, this study suggested that the paclitaxel-resveratrol PNPs cause a reduction of drug release in plasma and can reach the target site. 87 A study found that when MCF-7 and CAL-51 cells (human TNBC lines) were treated with TAM/RES-LbL-LCNPs, which are nanoparticles that deliver tamoxifen and resveratrol using a layer-by-layer approach and liquid crystalline nanoparticle technology, it resulted in the suppression of cell growth and the induction of cell cycle arrest specifically in the G0/G1 phase. The increasing solubility of resveratrol in the structure of the LCNP formula leads to an increased concentration near the cell, and as a result, cytotoxicity rises.…”
Section: Resveratrolmentioning
confidence: 99%
“…The % EE of the Qu-PMMs formulations was measured using the centrifugation technique, wherein 1 mL of Qu-PMM was centrifuged at 15,000 RPM for 30 min using a high-speed centrifuge. The 10 µL of supernatant was diluted with methanol, and Qu was estimated by the HPLC method [21]. The % EE was calculated by using the following Equation ( 1):…”
Section: Determination Of Percentage Entrapment Efficiency (% Ee)mentioning
confidence: 99%
“…E-TPGS has also been used as a prominent nanocarrier for curcumin to improve its anticancer activity on human colon cancer cells [20]. A previous study revealed that the Soluplus and E-TPGS polymeric nanoparticles improved in vitro cytotoxicity and in vivo biodistribution of paclitaxel and resveratrol [21]. Poloxamer 407 (Kolliphor ® P 407) is a block copolymer that contains ethylene oxide and propylene oxide with a low CMC value of 34.2 mg L −1 at 37 • C. The nanoparticles using Soluplus and poloxamer 407 have been reported to enhance the bioavailability of Qu [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on elucidating the delivery process of nano-DDS in vivo or in cells, including pharmacokinetics, drug distribution, excretion and cellular transport, endocytosis as well as intercellular trafficking. [6][7][8][9] The method to analyze behavior in vivo is to quantify a transported substance using liquid chromatography-mass spectrometry (LC-MS) or other quantitative instruments. For example, plasma pharmacokinetics and brain tissue distribution of zolmitriptan loaded chitosan nanoparticles in rats were presented by establishing an LC-MS assay to determine the content of zolmitriptan.…”
Section: Introductionmentioning
confidence: 99%